Determining the dimensions of the values of the moral leadership of the leaders of private schools in Jeddah city from the point of view of educational leadership expertise - Bajaber, Eman Said; Karim, Mona Khalid; Bajaber, Mohammed Abdullah (Journal of Educational and Psychological Sciences, 2022)
The study is an attempt to investigate the values of ethical leadership in private schools in Jeddah. The study discusses the obstacles of these leadership values. Delphi Technique method is used in this research to investigate the leadership values in three successful dependent rounds using surveys and personal interviews that were applied to a sample of (10, 17, 7) educational leadership experts. The results reveal a list of 35 ethical leadership values classified into three main dimensions and seven sub-categories. The result shows "respect" value gets 6% of discrepancy among the survey samples where the reason was “respect” cannot be distinguished sometimes from “compliment”. The lack of interest in selecting school leaders based on ethical leadership values and not providing sufficient guidance for school leaders are common obstacles that determined ethical leadership. The study recommends depending on ethical leadership evaluation in selecting school leaders would benefit the organization and resolve other leadership obstacles.